2007
DOI: 10.1007/s10165-006-0536-9
|View full text |Cite
|
Sign up to set email alerts
|

A case of SAPHO (synovitis-acne-pustulosis-hyperostosis-osteomyelitis) syndrome in which [18F]fluorodeoxyglucose positron emission tomography was useful for differentiating from multiple metastatic bone tumors

Abstract: We report the case of a 50-year-old Japanese woman with SAPHO (synovitis-acne-pustulosis-hyperostosis-osteomyelitis) syndrome. Radiographs showed osteosclerosis of the cervical and lumbar vertebrae, as well as osteosclerosis and osteolysis of the right femoral neck, resembling multiple metastatic bony lesions. Arriving at a diagnosis required hematological and imaging tests. Whole-body bone scintigraphy identified diffuse uptake from the lower cervical vertebrae to the lumbar vertebrae and marked uptake in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Although the radiographic features of SAPHO syndrome are very characteristic, sometimes a biopsy is necessary. Recently, reports have indicated that [ 18 F] FDG-PET is useful in distinguishing SAPHO syndrome from tumors [7][8][9]. In our case, the recent history of tuberculous lymphadenitis and MRI findings of destructive spondylodiscitis firmly supported a diagnosis of tuberculous spondylitis.…”
Section: Discussionsupporting
confidence: 67%
“…Although the radiographic features of SAPHO syndrome are very characteristic, sometimes a biopsy is necessary. Recently, reports have indicated that [ 18 F] FDG-PET is useful in distinguishing SAPHO syndrome from tumors [7][8][9]. In our case, the recent history of tuberculous lymphadenitis and MRI findings of destructive spondylodiscitis firmly supported a diagnosis of tuberculous spondylitis.…”
Section: Discussionsupporting
confidence: 67%
“…Prior case reports [16][17][18] have shown the utility of [ 18 F] FDG-PET/CT to differentiate active from healed chronic inflammatory lesions because PET/CT shows increased uptake only in lesions with active inflammation. The chronic osteosclerotic changes seen in our patients are hypothesized to represent a quiescent phase of the disease, which likely accounts for the normal FDG uptake in the 2 patients who had PET/CT scans in our series.…”
Section: Discussionmentioning
confidence: 99%
“…However, the accuracy rate of CTguided biopsy for spinal infections or tumors is only about 70% [14]. Takeuchi et al [15] reported that [(18)F]fluorodeoxyglucose positron emission tomography was useful for differentiating from multiple metastatic bone tumors. Court et al [2] described a case of a SAPHO syndrome in which percutaneous biopsies and thoracoscopic biopsies were needed to be done two times to make the final diagnosis.…”
Section: Discussionmentioning
confidence: 99%